The influence of borderline personality traits on clinical outcomes in bipolar disorder. (25th July 2020) - Saunders, Kate E. A.; Jones, Tomos; Perry, Amy; Di Florio, Arianna; Craddock, Nick; Jones, Ian; Gordon‐Smith, Katherine; Jones, Lisa
Abstract: Objectives: Systematic reviews suggest comorbid borderline personality disorder is present in approximately 20% of individuals who have bipolar disorder, but current diagnostic systems demonstrate a move towards dimensional rather than categorical approaches to classifying personality pathology. We aimed to examine the presence and severity of borderline personality traits in bipolar I and bipolar II disorder, and to explore associations between the presence/severity of borderline personality traits and clinical outcomes in bipolar disorder. Methods: Borderline personality traits were measured in 1447 individuals with DSM‐IV bipolar disorder (1008 bipolar I disorder and 439 bipolar II disorder) using the Borderline Evaluation of Severity over Time (BEST) questionnaire. Lifetime clinical outcomes were assessed via Schedules for Clinical Assessment in Neuropsychiatry (SCAN) semi‐structured interview and clinical case notes. Results: Borderline personality traits were common in both bipolar disorder groups, with 86.2% participants reporting at least one trait. These included traits that overlap with (eg mood instability) and those that are distinct from the symptoms of bipolar disorder (eg fear of abandonment). Borderline personality traits were significantly more frequent and more severe in bipolar II disorder compared to bipolar I disorder. More severe borderline traits, and even the presence of a single borderline personality trait, were significantly associated with younger age of bipolar disorder onset and higher prevalence of lifetime alcohol misuse in both bipolar disorder groups. Conclusions: The presence of comorbid borderline personality traits should be considered in the management of all patients with bipolar disorder irrespective of whether criteria for a categorical borderline personality disorder diagnosis are met.